Mirabegron and antimuscarinics for treating ureteral stent-related symptoms: a systematic review and meta-analysis of RCTs - Lu, Youyi; Li, Qi; Zou, Qingsong; Cui, Yuanshan (Frontiers in Pharmacology, 2023)
Objective: We conducted a meta-analysis to assess the efficacy and safety of mirabegron (50 mg/day) and antimuscarinics for treating ureteral stent-related symptoms (SRSs). Methods: All randomized controlled trials (RCTs) were identified by searching PubMed, Embase, Web of Science, and Cochrane Library. Rev Man version 5.3.0 was used for statistical analysis. Results: This meta-analysis included five RCTs involving 317 patients. A fixed-effect model revealed that mirabegron was superior to antimuscarinics in urinary symptoms (MD -1.39, 95% CI -2.63 to -0.15, p = 0.03) and general health (MD -1.65, 95% CI -2.60 to -0.69, p = 0.0007) one week after treatment initiation. We observed no significant differences in body pain (MD 0.05, 95% CI -1.06 to 1.15, p = 0.94), work performance (MD -0.86, 95% CI -1.77 to 0.06, p = 0.07), and sexual matters (MD 0.03, 95% CI -0.77 to 0.83, p = 0.94). Two weeks after treatment initiation, the Ureteral Stent Symptom Questionnaire (USSQ) revealed no significant differences between the two groups. The mirabegron group demonstrated a significant improvement in quality of life (MD -0.18, 95% CI -0.34 to -0.01, p = 0.03), while IPSS did not reveal a significant difference between the two groups (MD -0.74, 95% CI -1.79 to 0.32, p = 0.17). Regarding safety, a pooled data analysis presented that the incidence of constipation was lower in the mirabegron group (OR 0.10, 95% CI 0.01 to 0.77, p = 0.03). Mirabegron and antimuscarinics groups did not differ significantly concerning the risk of dry mouth (OR 0.15, 95% CI 0.02 to 1.27, p = 0.08). Conclusions: Mirabegron is superior to antimuscarinics in alleviating ureteral SRSs and improving quality of life. Additionally, mirabegron 50 mg/day presented safety with a lower incidence of constipation.